Administered development: the fifth decade 1990s - Henderson, Keith M; Dwivedi, O.P
The authors survey, from the angle of Comparative and Development Administration, the impact of over four decades of involvement of indigenous public administrators, often with external aid, in the process of nation building and socio-economic development (they term this invelvement as "administered development"). The authors seek to assess the emerging situation of administrative culture and morality being materialised in such nations; and project dilemmas and responses for the 1990s, looking towards the 21st century. They basically seek to articulate a new approach for Comparative and Development Administration in this article - Reproduced.
Keywords: Public Administration; Development Administration